PENGARUH TERAPI PSIKORELIGIUS DZIKIR UNTUK MENURUNKAN SALAH SATU TANDA DAN GEJALA DARI SKIZOFRENIA YAITU HALUSINASI PENDENGARAN DIWILAYAH KERJA UPTD PUSKESMAS KONCARA KABUPATEN PURWAKARTA - Yuli Erlina,; Suci Hardianti,; Efhal Rhevaldy, (Journal of Innovation Research and Knowledge, 2025)
Auditory hallucinations are one of the main symptoms in schizophrenia patients which often cause emotional distress and maladaptive behavior. Psychoreligious approaches such as dhikr therapy are believed to help reduce the intensity of hallucinations by increasing mental calm and spiritual strengthening of patients. To determine the effect of implementing dhikr psychoreligious therapy on reducing the intensity of auditory hallucinations in schizophrenia patients in the working area of ​​the Koncara Community Health Center UPTD, Purwakarta Regency. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample size was 30 respondents with a purposive sampling technique. The intervention in the form of dhikr therapy (istighfar, tasbih, tahmid, and tahlil) was carried out for 7 consecutive days, twice a day (morning and evening). Measurement of hallucination intensity was carried out using a hallucination intensity observation sheet before and after the intervention. Data analysis used the Wilcoxon Signed Rank Test. The average hallucination score before therapy was 16.4, and after therapy it decreased to 10.2. The Wilcoxon test results showed a p-value of 0.000 (<0.05), indicating a significant difference between before and after dhikr therapy. Conclusion: Dhikr psychoreligious therapy is effective in reducing the intensity of auditory hallucinations in schizophrenia patients. This therapy can be used as a non-pharmacological intervention to support the healing process of patients with mental disorders.